Peran Manajemen Sekolah dalam Mengembangkan Pendidikan Berbasis Budaya Lokal Studi Sekolah Dasar Negeri 01 Karanggondang - Firda Mawaddatul Jannah; Muhammad Ridwan; Naili Azkiya Sari; Munawarotus Sholihah; Nur Rohman (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe the role of school management in developing local culture-based education. Local culture-based education is a learning approach that integrates local cultural values as a contextual, relevant, and meaningful learning resource for students. This study used a qualitative approach with a case study method in an elementary school that has successfully implemented local culture comprehensively in various aspects of learning activities. Data were collected through in-depth interviews, observations, and documentation studies. The results show that school management plays a strategic role in formulating policies, supporting culture-based learning programs, and establishing partnerships with the community for cultural preservation. The principal, teachers, and education staff actively integrate local cultural elements into the curriculum, extracurricular activities, and the learning environment. Despite facing challenges such as limited resources and lack of training for educators, this school is able to demonstrate a strong and consistent commitment to making local culture the foundation for character and identity formation for students. This study confirms that collaboration between stakeholders is key to success in realizing education rooted in local wisdom. By involving parents and the community, schools can create a more inclusive and supportive learning environment. These findings demonstrate that community involvement in the educational process not only enriches students' learning experiences but also strengthens their sense of belonging to local culture. This research significantly contributes to the development of educational models that focus not only on academic aspects but also on the development of student character and identity rooted in local cultural values. Through this approach, it is hoped that students will grow into individuals who are not only academically intelligent but also have an awareness and appreciation for their own culture.